2016
DOI: 10.1155/2016/3159617
|View full text |Cite
|
Sign up to set email alerts
|

The Difference between the Two Representative Kampo Formulas for Treating Dysmenorrhea: An Observational Study

Abstract: In Kampo medicine, two different formulas are effective for treating dysmenorrhea—tokishakuyakusan and keishibukuryogan; however, the criteria by which specialists select the appropriate formula for each patient are not clear. We compared patients treated with tokishakuyakusan and those with keishibukuryogan and proposed a predictive model. The study included 168 primary and secondary dysmenorrhea patients who visited the Kampo Clinic at Keio University Hospital. We collected clinical data from 128 dysmenorrhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Higher efficacy rates are expected with longer treatment periods. Studies conducted on ibuprofen (Brufen) and naproxen (Naixan) have reported almost the same efficacy rates . We also observed a high efficacy rate with respect to other symptoms within the Kampo treatment term.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Higher efficacy rates are expected with longer treatment periods. Studies conducted on ibuprofen (Brufen) and naproxen (Naixan) have reported almost the same efficacy rates . We also observed a high efficacy rate with respect to other symptoms within the Kampo treatment term.…”
Section: Discussionsupporting
confidence: 74%
“…We also showed that Kampo treatment caused some adverse reactions, but the reactions were mild and resolved after stopping or even continuing the Kampo formulas. In the aforementioned studies on ibuprofen (Brufen) and naproxen (Naixan), side‐effect rates of 3.04% and 3.50%, respectively, were noted . Studies on the safety of OC have reported overall adverse outcome rates of 96.6–100% for drospirenon/ethinylestradiol betadex (Yaz) and 25–41.9% for norethisterone/ethinylestradiol (Lunabell), with some patients experiencing moderate or severe adverse reactions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pattern diagnosis, which not only considers symptoms of a patient but also the complexion and physique, is important when administering herbal medicine. In TEAM, various diagnostic methods have been used to administer herbal formulas, including a “cold-heat/deficiency-excess pattern” diagnosis [ 34 36 ]. GCB is a traditionally used herbal medicine for patients with pain and has been primarily prescribed for patients with poor nutrition and a skinny, cold intolerance tendency [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…TSS has been mainly used for women who have dysmenorrhea or ovarian dysfunction, which can be used for pain alleviation or estrogen-secreting qualities. 3,4 In addition, accumulated evidence of its neuroactive and neuroprotective effects was verified. [5][6][7] Currently, the mechanisms of TSS have been reported to involve immunological effects on murine endometriosis and pregnancy loss model.…”
Section: Introductionmentioning
confidence: 93%